Soft-switching active-clamp flyback microinverter for pv applications / Rasedul Hasan - Rasedul, Hasan (2017)
Grid-connected photovoltaic (PV) system has received a great attention due to the elimination of battery cost in distributed power generation system. The microinverter is superior to other technologies of PV converter in terms of obtaining the highest maximum power point tracking (MPPT) accuracy on each PV module. The microinverters can be classified into isolated and non-isolated type with respect to the presence of galvanic isolation. Isolated types are more preferable in terms of reliability and transferring higher quality of power to the grid. However, the efficiency of the isolated microinverters degrades due to high frequency transformer and high switching losses. Therefore, increasing the efficiency of the PV converter maintaining higher lifetime and lower cost is the most critical job to form a reliable microinverter. This study presents a single-stage and a double-stage active-clamp resonant flyback microinverter for grid-connected PV AC module system. The single-stage microinverter is operated with a hybrid operation of discontinuous conduction mode (DCM) and boundary conduction mode (BCM). The proposed modified hybrid method is based on different variable negative current references for DCM and BCM operation. Hence, the zero-voltage and zero-current switching (ZVZCS) turn-on of the high frequency main switch is achieved by allowing a negative current through the resonant circuit in both conduction modes. A small capacitor is inserted across the primary switch to achieve zero voltage switching (ZVS) turn-off operation. The energy stored in the leakage inductance of the transformer is also recycled and voltage stress of the main switch is reduced. It enables the use of lower voltage rating MOSFET and reduces the switch conduction loss. The mathematical analysis of the proposed hybrid operation modes in different resonant condition is provided for the modelling of the proposed system. The double-stage microinverter is composed of a DC-DC flyback converter with a resonant full-bridge inverter. The flyback converter contains a resonant active-clamp circuit that limits the voltage stress and provides soft-switching operation. Therefore, the switching losses of the high frequency primary switches are negligible. A resonant full-bridge inverter with ZVS of the high frequency switches is adopted that make the overall efficiency high. Moreover, using a film capacitor in the DC link, the lifespan of the microinverter is increased. A 250W prototype of the proposed microinverter has been implemented and the peak efficiencies are found to be 97.1% and 96.5% for the single- and double-stage microinverter respectively. Hence, the proposed active-clamp flyback microinverter confirms the superiority compare to existing topologies.